Materialities as a foundation for teaching work in Early Childhood Education - Lidiane Pereira Evangelista; Camila Vieira da Rosa Alves; Julice Dias (Universidade Federal do Norte do Tocantins, 2023)
This article aims to present reflections about the analysis of the curricular relationship between the structural elements of teaching with babies and the materialities present in the planning of teachers of the Municipal Education Network of Florianópolis, based on a research at the Master's level in the Municipal Centers of Early Childhood Education. The sources are the official and legal documents that guide the care and education of babies, very young children and young children. And as a theoretical support, it is anchored in the production that focuses on the specificity of teaching with babies, the organization of spaces, environments and materialities in and for Early Childhood Education. The study affirms the importance and curricular meaning of the materialities arranged to babies in the organization of pedagogical work.